COMPOSITION-PROPERTY CORRELATION IN LITHIUM MICAS - Skosyreva M.V.; Vlasova Y.V. (My University, 1988)
This study of lithium micas has shown that the increase in number of occupied octahedral positions in them clearly depends on their lithium content. The sum of octahedral cations (Y) gradually increases from protolithionite, via zinnwaldite, to lepidolite and polylithionite and, in the last two minerals, is proportional to their lithium content. It seems to us that not only does aluminum, as mentioned above, affect the ordering of the octahedral layer, but also that the polarizability of lithium could affect the distortion and the deformation of tetrahedra and, indirectly, the extent of ordering in the tetrahedral and octahedral layers. That effect will become more marked as the lithium content and, accordingly, the number of occupied octahedral positions increase. The dependence of the distortion of tetrahedron on the polarizing effect of lithium and of the number of occupied octahedral positions in the micas on its content shows up clearly in their IR spectra, as does the effect of domain-type or statistical distribution of lithium and aluminum in their octahedral layers.